PRACTICUMMA: AN OPEN PLATFORM FOR ONLINE PRACTICUM AT ELEVENTH GRADE SCIENCE STUDENTS - Kismunthofiah, Kismunthofiah; Purnamaningrum, Arifah; Norra, Bunga Ihda (Jurnal Pendidikan Matematika dan IPA, 2023)
Abstract During the online learning period, students experience many obstacles that cause the practicum to not run well, especially for schools with problems with laboratory facilities. Students also needed media that could be used for independent and repetitive learning. Therefore, the researcher developed the Practicumma website by integrating learning components (learning resources, teaching materials, media, methods evaluation) for online practicum. The research objective was to develop a biology learning website for the eleventh-grade science students. The type of research used is RD (Research and Development) with the ADDIE development model. Data analysis using qualitative and quantitative methods. The results showed that Practicumma was suitable for use in biology practicum according to the assessment of media experts at 76.7%, material experts at 80%, biology teachers at 83.53%, and limited scale test to students at 87.2%, so the average percentage of eligibility was 81.86% (very valid).